Grammatic Communication Between Joint Components - Abdurayim Turobov (International Journal of Advanced Science and Technology, 2020)
In this article both syntactic relation and semantic relation among the components of compound word were observed according to small syntax issues. Moreover, this information about the lingvistic nature was given. According to syntactic point of view, it was scientifically proven that the grammatic relation among the components of compound word remains in the static state both when it is used in the composition of the sentence and when it is taken independently.